2014
DOI: 10.5539/ijms.v6n1p103
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Political-Legal Forces on Jordanian Industrial Exports in the Private Sector

Abstract: This study aims to measure the Influence of Political-Legal forces, which both are elements in the marketing external environment, on Jordanian exporting performance. The researchers employed the experimental approach in conducting the study and the applications of this approach including statistical analysis of data collected for the field study. The population of the sample comprises marketing managers in Jordanian exporting companies. Questionnaires were distributed over a convenience sample that amounted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Newman, C. et al (2016); IEG, S. O. (2013); Wangwe, S. et al, (2014); Hashem and Irshaidat (2014), who argue that political-legal forces have a direct impact on manufacturing firms'. The survey results were consistent with the argument of (Zeb, N., et al, 2014;Fiestas and Sinha, 2011;Ihugba, O.…”
Section: Investment Climate Constraints Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newman, C. et al (2016); IEG, S. O. (2013); Wangwe, S. et al, (2014); Hashem and Irshaidat (2014), who argue that political-legal forces have a direct impact on manufacturing firms'. The survey results were consistent with the argument of (Zeb, N., et al, 2014;Fiestas and Sinha, 2011;Ihugba, O.…”
Section: Investment Climate Constraints Discussionmentioning
confidence: 99%
“…There was also a close relationship between various types of pollution and diseases. Recent empirical studies Hashem and Irshaidat (2014) conducted in Jordan, found that political and legal factor had a negative effect on industrial export performance. Wangwe, S, et al, (2014) conducted a study on the constraints and challenges facing the emerging manufacturing firms.…”
Section: Empirical Literaturementioning
confidence: 99%